Evaluación del Efecto de tres Herbicidas Selectivos con Tres Dosis para el Control de Malezas en el Cultivo de Quinua (chenopodium quinoa willd) en pre-emergencia Salache, Latacunga, Cotopaxi 2019. - Taipicaña Comasanta, Carmen Viviana (2019)
The present research project was carried out in Latacunga canton, Eloy Alfaro parish, Salache Bajo neighborhood, at Technical University of Cotopaxi, in the Experimental and academic campus Salache with geographical coordinates of 00º 59 '57' 'south latitude and 78º 37' 14 '' West length, the main objective was to evaluate the effect of three selective herbicides with three doses for the control of weeds in the cultivation of quinoa (Chenopodium quinoa Willd) in pre-emergency. The herbicides linuron, atrazine and Haloxyfop- methyl at three application doses which were: 0.25 cc; 0.5 cc and 1 cc per liter of water. The indicators to be evaluated were: weed cover index, germination percentage, plant height, number of leaves and stem diameter. An experimental model of block design was applied completely randomly, applying the 5% Tukey Test for the sources of variation that present significant differences, the statistical analysis was performed using the Infostat 2018 statistical software, the results of the research were following: weed species were identified before and after planting, Urtica dioica, Pennisetum clandestinum, Taraxacum officinale, Chenopodium álbum, Sphaeralcea bonariensis, Sonchus oleraceus y Galinsoga parviflora, siendo la especie Sonchus oleraceus, the most dominant species with a percentage of 23.1% before planting and 13.9% after planting, for the germination percentage it is observed that the control treatment shows high values at both 7 and 10 DDS with 63, 63% and 66.9% respectively, while for herbicides, Linuron averaged 57.71% and 60.58% in the percentage of germination winning the other herbicides.